Of Soukhuan and Laos - Chai, Elena Gregoria Chin Fern (Kota Samarahan : Faculty of Social Sciences, Universiti Malaysia Sarawak, 2006)
Modern societies need ritual elaborations as much as they need science (Ernest Gellner,1992 :91). As Gellner puts it, "ritual now mirrors, not the real situation, but the past or fictitious distribution of social power in Laos". The soukhuan is the most ubiquitious of all occasions and celebrations, according to a Lao scholar, Phoumirath (2002) in his paper titled Laoness Performed : Rituals, Memory and Identity In Laos Wedding.